Hubungan antara ukuran-ukuran tubuh dengan bobot badan kambing Peranakan Etawah jantan di Kabupaten Klaten (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
The objective of the research was to determine the relationship between body weight and body measurement of Peranakan Etawah (PE) goat male at different age in Klaten Regency. The research was conducted in District Karangnongko and Kemalang. The research used 98 male goats aged 0-60 months and the data were analyzed using correlation and regression. The study found a very positive relationship between the chest girth, the body length, shoulders height, chest depth and body weight on goats aged 0-6 months until 12-24 months of age. Another findings were goats with 24-36 months of age had a very positive relationship between chest girth and the body length with body weight, while shoulders height and chest depth had a positive correlation with body weight. A very positive relationship was also found on the chest girth with body weight of goats with age of 36-60 months, while other body measurements had a very low positive relationship. The study concluded that chest girth had a close correlation with body weight of the PE goat. Keywords: Body measurements, body weight, Peranakan Etawah